2013
DOI: 10.1002/art.38113
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Baseline Levels of Erythrocyte Folate With Treatment Nonresponse at Three Months in Rheumatoid Arthritis Patients Receiving Methotrexate

Abstract: Objective. To investigate whether baseline concentrations of one-carbon metabolism biomarkers are associated with treatment nonresponse and adverse events in rheumatoid arthritis (RA) patients receiving methotrexate (MTX).Methods. A prospective derivation cohort (n ‫؍‬ 285) and validation cohort (n ‫؍‬ 102) of RA patients receiving MTX were studied. Concentrations of plasma homocysteine, serum vitamin B 12 , serum folate, erythrocyte vitamin B 6 , and erythrocyte folate were determined at baseline and after 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
1
27
1
2
Order By: Relevance
“…Reductions in folates occurred despite supplementation with folic acid in 47% of patients receiving MTX. This finding is in contrast to studies that have found folic acid supplementation to prevent reductions in RBC and plasma folates that occur secondary to MTX therapy (19, 42). Although the reason for this apparent discrepancy is unclear, it is important to point out that this study differed in a number of ways from the previous studies, including: its cross-sectional design, patient population (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Reductions in folates occurred despite supplementation with folic acid in 47% of patients receiving MTX. This finding is in contrast to studies that have found folic acid supplementation to prevent reductions in RBC and plasma folates that occur secondary to MTX therapy (19, 42). Although the reason for this apparent discrepancy is unclear, it is important to point out that this study differed in a number of ways from the previous studies, including: its cross-sectional design, patient population (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Beyond clinical parameters (body mass index, smoking) and baseline disease severity, genetic factors that were associated with unresponsiveness to MTX included SNPs in the efflux transporters ABCB1 (rs1045642 G > A) and ABCC3 (rs4793665 T > C), and methionine synthesis (MTRR, rs1801394 A > G) [90,91]. Furthermore, low baseline erythrocyte folate and erythrocyte MTX-polyglutamate levels after 3 months of treatment were predictive for a decreased MTX response [92]. None of these biomarkers was associated with adverse effects of MTX treatment.…”
Section: Antifolates In Immune Diseasesmentioning
confidence: 97%
“…Действительно, име-ются данные, что клинический эффект лечения МТ у боль-ных РА коррелирует с уровнем МТПГ в эритроцитах [56]. Важно, что низкий базальный уровень фолатов в эритро-цитах ассоциируется с высокой активностью РА и отсутст-вием эффекта на фоне лечения МТ в течение первых 3 мес терапии [57]. Также было показано, что прием ГК ассоци-ируется с более высоким накоплением МТПГ в эритроци-тах, что в свою очередь коррелирует со снижением актив-ности РА [58].…”
Section: полиглютамирование метотрексатаunclassified